Penalaran Dalam Karya Ilmiah Mahasiswa Ditinjau dari Perspektif Gender - Lida, Ulfah Mey (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Reasoning in student scientific work mostly places the conclusion at the beginning of the paragraph. This shows that based on its complexity, deductive reasoning still dominates the structure of students' writing. However, as students at the highest level, students should be able to produce various complexities of reasoning. This research aims to describe the building blocks of reasoning in students' scientific work from a gender perspective. This research uses a qualitative approach. The research data is in the form of texts in student scientific works consisting of 100 articles written by 50 male students and 50 female students in the Sharia Business Management, Sharia Accounting, Sharia Banking and Sharia Economics Study Program at the Faculty of Islamic Economics and Business, IAIN Holy. The data collection method in this research is the observation method. Data analysis uses the Holsti communication content analysis model. Based on the results of the analysis, it can be concluded that the elements that build reasoning in the scientific work of male and female students have differences in the selection of elements that build reasoning when presenting arguments. The difference lies in providing evidence for the position conveyed. Men tend to provide evidence in the form of opinions, while women provide evidence in the form of facts.